2014
DOI: 10.1016/j.canlet.2014.01.014
|View full text |Cite
|
Sign up to set email alerts
|

mTOR is a promising therapeutical target in a subpopulation of pancreatic adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains a highly lethal disease, unusually resistant against therapy. It is generally felt that stratification of patients for personalized medicine is the way forward. Here, we report that a subpopulation of PDACs shows strong activation of the mTOR signaling cassette. Moreover, we show that inhibition of mTOR in pancreatic cancer cell lines showing high levels of mTOR signaling is associated with cancer cell death. Finally, we show using fine needle biopsies the existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The limitations of the study are its retrospective design, the associated bias and the small number of samples in the study in pancreatic cancer patients with diabetes who underwent pancreatic cancer resection. It has been documented that whether patients benefit from mTOR inhibitor depends on the status of mTOR activation in patients with pancreatic cancer 54 , and P70S6K has been documented to be the major direct target of mTORC1 that mediates the anticancer actions of mTOR inhibitors 14 . Thus, patients with P70S6K signaling activation should benefit more from metformin.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of the study are its retrospective design, the associated bias and the small number of samples in the study in pancreatic cancer patients with diabetes who underwent pancreatic cancer resection. It has been documented that whether patients benefit from mTOR inhibitor depends on the status of mTOR activation in patients with pancreatic cancer 54 , and P70S6K has been documented to be the major direct target of mTORC1 that mediates the anticancer actions of mTOR inhibitors 14 . Thus, patients with P70S6K signaling activation should benefit more from metformin.…”
Section: Discussionmentioning
confidence: 99%
“…The mTOR pathway is constitutively activated in 25%-75% of human PDAC tumors and mTOR inhibition can lead to proliferation arrest of PDAC cells [ 143 ]. Rapamycin induces autophagy in rapamycin-sensitive pancreatic cell lines only, which suggests that autophagy induction may be a downstream consequence of the antitumor effects of mTOR inhibitors [ 144 , 145 ]. Recent results from phase II clinical trials of mTOR inhibitors in PDAC patients failed to demonstrate clinical benefit [ 146 , 147 ].…”
Section: Targeting Metabolism In Pancreatic Cancermentioning
confidence: 99%
“…Given the up-regulation of the mTOR pathway in many chemoresistant cancer [2] , mTOR inhibitors provide a logical solution to re-sensitize tumor cells to chemotherapy or to delay the development of resistance to treatment. Recent studies have demonstrated the effectiveness of sirolimus (rapamycin) in solid tumors, such as metastatic breast [3] , pancreatic [4] , and renal carcinomas [5] . Sirolimus is a first generation mTOR inhibitor [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%